Strategi Branding Nagari Sungai Jambur melalui Pengembangan Nagari Creative Hub Berbasis Digital - Sella Puspita; Aidil Adha; Geo Satria Singara; Azfa Jovaren Syahrilian (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
Nagari Sungai Jambur possesses various creative economic and cultural potentials, including Banun Songket weaving, Tenun Padi Sarumpun, Batik Bacolok, galo-galo honey production, and local culinary enterprises. However, these potentials are still developed independently and have not been integrated into a comprehensive branding strategy to strengthen the village’s identity. This study aims to develop a branding strategy for Nagari Sungai Jambur through a digital-based Nagari Creative Hub concept. A descriptive qualitative approach was employed, with data collected through observation, in-depth interviews, documentation, and spatial mapping. The results indicate that the Creative Hub approach can integrate economic and cultural potentials into a unified creative ecosystem that strengthens nagari identity. Spatial mapping supports regional planning by identifying strategic locations, MSME distribution, public facilities, and cultural assets. Digitalization through social media, visual design, and the development of the Nagari Creative Hub Book enhances local product visibility and sustainable branding. A participatory approach involving the village government, MSME actors, youth, and the community supports creative economic development based on local potential. Thus, a digital-based Nagari Creative Hub is an effective strategy to strengthen regional identity, improve local product competitiveness, and promote sustainable village economic development.